TRANSFORMASI BISNIS TEMPO MEDIA GROUP MENUJU KONVERGENSI MEDIA - Ginjara, Yohanes Ray; Widiartanto, Widiartanto Widiartanto (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
The media industry revolution is quite large and the results are already visible. Some newspaper and magazine publishers eventually closed and stopped production, while others still survived by preparing a new strategy of migrating publishing platforms to digital space, because the use of internet technology so rapidly and become a new culture. Tempo Media Group has made several changes in its business strategy. This study aims to describe the steps taken by Tempo Media Group in carrying out its business transformation towards media convergence during 2012-2015. This study uses descriptive qualitative methods to find out in depth how Tempo Media Group's management strategy in developing Tempo.co online media. The results showed that Tempo Media Group used a strategy by transforming into digital media and by continuing to maximize revenue from the print media business. The steps taken include improving the appearance of the Tempo.co site and strengthening the content. This convergence strategy must be accompanied by changes in behavior of all corporate entities. Being adaptive, observing each change intelligently, is a prerequisite for winning competition in the current era of digital media. Company management must to maintain a commitment to the values of independence, professionalism, and integrity in reporting news.